Multiple Criteria Model Study of Outsourcing Service Countries in the East and Southeast Asia - Massoud Moslehpour; Van Kien Pham (International Journal of Supply Chain Management, 2017)
Research background: Outsourcing decisions are very a complex and multifaceted process because decision-makers (DMs) have to make a complete evaluation considering multiple criteria which often may conflict with each other. The evaluation of outsourcing destination, then, basically is a multi-criteria decision making problem (MCDM). Overtime a great number of works have been carried out regarding this field. Unfortunately, few of them focus on solving the outsourcing problems. Objectives: The purpose of this paper is to address the research gap by first reviewing the literature of MCDM methods and then constructing a simple MCDM-based model to help managements evaluate and select the best outsourcing location for their companies. Materials and methods: This study utilizes the Analytic Hierarchy Process (AHP) approach to ratify the effectiveness of the MCDM-based model. Seven typical emerging countries are chosen from the East and Southeast Asian regions. To compute the final weight for each country, we asked for the opinion of 12 experts in the given field. Result: The results of the empirical study show that among seven promising countries in East and Southeast Asia, China is the best country for the provision of outsourcing services in terms of cost competiveness and business environment. Generally, the MCDM model for outsourcing problems in this study works well in reality, especially with the case of the East and Southeast Asian region. Conclusion: This research provides several significant outsourcing theories and practices for decision-makers when selecting outsourcing destinations.